Inter-species Agouti Signaling Protein (ASIP) Polymorphism Using Phylogeny Analysis - Tirtosari, D R; Febriani, A S; Wardhani, Erintha E; Siwi, Putih J (Bioinformatics and Biomedical Research Journal, 2018)
Variability of colour phenotypes in animal have encoded by agouty signaling protein (ASIP) and melanocortin 1 receptor (MC1R) gene polymorphisms and the pigmentation is afected by extension and agouti loci affect. Mutation in ASIP have been reported to completely eliminate the function or expression of the ASIP protein, this caused by a complete or several absence of alternative switch between eumelanin or pheomelanin syntesis and result only one of their to produce pigment. We collected nucleotide and protein sequence ASIP CDS from 7 specieses in gene bank and use a phylogenetic tree to know the distance of genes. The conserved regions lies on position 602-617 bp with consensus of 602 TGAACAAGAAATCCAA 617 which is the evidence of close taxonomic relation. Variation analyze show polimorfic white colour (G/T) black colour, white colour in Equus caballus (T/A). We found a polymorphic regions that explain the corelation to coat colour sgnaling in animal. Keywords: ASIP, Coloring, Mutation, Phenotype, Polymorphism.